Strategi dan Tantangan Guru PAI Dalam Mengimplementasikan Kurikulum Merdeka di MAS Darussyariah Kota Banda - Evi Nurhovivah; Silahuddin; Zulfatmi Budiman (Al-Mudarris, 2026)
This study examines the implementation of the Merdeka Curriculum in Islamic Religious Education (Pendidikan Agama Islam/PAI) learning at MAS Darussyariah, where the curriculum has been implemented for the past two years. However, field findings indicate that PAI teachers have not yet fully optimized the implementation of the Merdeka Curriculum in instructional practices. This study aims to analyze the challenges faced by PAI teachers and identify the strategies employed to optimize the implementation of the curriculum. The research employed a descriptive qualitative approach, with data collected through interviews, observations, and documentation. Learning documents such as teaching modules, instructional media, and assessment instruments were used for triangulation and to evaluate the alignment between instructional planning and classroom practice. The findings reveal that the challenges experienced by PAI teachers include limited understanding of the Merdeka Curriculum, difficulties in designing differentiated teaching modules, diverse assessment demands, insufficient professional training, limited facilities and infrastructure, and the need to adapt learning practices to the era of modernization while maintaining Islamic values. The strategies implemented include improving teachers’ competencies through training programs, applying flexible and digital-based learning approaches, integrating Islamic values into instructional processes and the Pancasila Student Profile, as well as implementing authentic assessment. This study provides practical implications for strengthening instructional processes in PAI learning to support the effective implementation of the Merdeka Curriculum.